(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The removal by surgery of a limb (arm or leg) or other body part because of injury or disease, such as diabetes or cancer.Below-knee and above amputation are the most commonly performed major amputations. Below-knee amputations may be carried out using either a long posterior flap or skewed flaps. Successful use of prostheses after lower-limb amputation (LLA) depends on undergoing physiotherapy and rehabilitation both physically and psychologically. Lower extremity (LE) amputation patients who use prostheses have gait asymmetries and altered limb loading and movement strategies when ambulating. Subsequent secondary conditions are believed to be associated with gait deviations and lead to long-term complications that impact function and quality of life as a result.